Investigating the Relation between Syntactic Complexity and Subgenre Distinction - A Case Study on Two Contemporary French Authors - Hesselbach, Robert (Digital Stylistics in Romance Studies and Beyond, 2024)
The purpose of this article is to explore the ways in which the analysis of the syntactic complexity of a text’s sentences can help distinguish between works belonging to different literary subgenres written by the same author. Based on the considerations of an earlier study (Hesselbach 2019), syntactic complexity is understood here as an array of qualitative as well as quantitative features. Applying this method to a corpus of two contemporary French authors and their novels (1979–2002), comprising both crime fiction (roman policier) and ‘high literature’ (littérature blanche), the results of this study show that syntactic complexity has very little influence on genre distinction, at least for the two subgenres examined. In fact, a very stable distribution of results can be observed in both qualitative and quantitative terms. Furthermore, the evidence suggests that the degree of syntactic complexity is more likely to appear as an author-related characteristic.<br
Keywords: syntactic complexity; (sub)genre distinction; French novel; Yasmina Khadra; Jean Echenoz